PENGARUH PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN BERPIKIR SISWA DI SANGGAR PANDAN MALAYSIA - Anggraini, Nopa Pade; Syamsuyurnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the impact of Project-Based Learning (PBL) implementation on students' thinking skills at Sanggar Pandan Malaysia. The research employed a quasi-experimental design with 12 students as participants, divided into experimental and control groups. Data collection utilized pre-test and post-test measurements of critical thinking, creative thinking, and problem-solving skills through standardized thinking skills assessment instruments. The findings revealed significant improvements in students' thinking skills, with the experimental group showing enhanced collaborative learning, problem-solving abilities, and critical thinking capabilities compared to the control group. Statistical analysis indicated significant differences (p < 0.05) between pre-test and post-test scores in the experimental group. The study concludes that PBL effectively enhances students' higher-order thinking skills through real-world problem-solving activities and collaborative learning environments. These findings contribute to educational practices in Malaysia, particularly in developing 21st-century skills among students.